Focused clamping of a single neuronal SNARE complex by complexin under high mechanical tension - Min Ju Shon (Nature Portfolio, 2018)
The SNARE complex enables the fusion of synaptic vesicles with presynaptic membrane via a zippering process that is modulated by the protein complexin, though the precise mechanism remains unclear. Here, the authors used magnetic tweezers to show how complexin prepares a SNARE complex for fusion under mechanical tension.